Lightning‐initiator type of narrow bipolar events and their subsequent pulse trains. Issue 12 (30th June 2014) - Wu, Ting; Yoshida, Satoru; Ushio, Tomoo; Kawasaki, Zen; Wang, Daohong
Abstract Previous observations show that some narrow bipolar events (NBEs) can initiate intracloud discharges, but the role of NBE as lightning initiation is still unclear. During the summer of 2013, 827 NBEs were detected with a 3‐D LF lightning location system in Osaka, Japan. Out of 638 positive NBEs, 103 occurred as the initial events of lightning flashes. These initiator‐type NBEs, called "INBEs" in this paper, are always followed by positive pulse trains whose locations show upward propagations probably from the main negative charge region to the upper positive charge region. Most of INBEs develop into intracloud flashes. Only two INBEs develop into positive ground flashes and five INBEs develop into negative ground flashes. Pulse widths and peak amplitudes of electric field change waveforms of INBEs are almost the same as those of normal NBEs. A major difference is that INBEs have much lower discharge heights. Most of INBEs are lower than 10 km while normal NBEs are mainly higher than 10 km. Characteristics of positive pulse trains following INBEs are closely related with discharge heights of INBEs. Higher INBEs are usually followed by weaker, fewer, and less frequent positive pulses with slower upward propagations. As the height increases to above 10 km, NBEs are usually no longer followed by such positive pulses.